1998
DOI: 10.1017/s0022112097007829
|View full text |Cite
|
Sign up to set email alerts
|

On the acoustic levitation of droplets

Abstract: This paper deals with the theoretical and experimental investigation of acoustically levitated droplets. A method of calculation of the acoustic radiation pressure based on the boundary element method (BEM) is presented. It is applied to predict shapes of droplets levitated in an acoustic field (and as a result, deformed by it). The method was compared with several known exact and approximate analytical results for rigid spheres and shown to be accurate (and a widely used approximate form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
114
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(117 citation statements)
references
References 17 publications
3
114
0
Order By: Relevance
“…Indeed, during the levitation of droplets this represents a typical shape (Yarin et al 1998). As seen in figure 4, the axial force induces a compression of the droplet along its semiminor axis a, while the radial force stretches the droplet along its semimajor axis b.…”
Section: Viscous Medium-cfd Model: Ellipsoidmentioning
confidence: 96%
See 1 more Smart Citation
“…Indeed, during the levitation of droplets this represents a typical shape (Yarin et al 1998). As seen in figure 4, the axial force induces a compression of the droplet along its semiminor axis a, while the radial force stretches the droplet along its semimajor axis b.…”
Section: Viscous Medium-cfd Model: Ellipsoidmentioning
confidence: 96%
“…Owing to its material independency, acoustic levitation has found a wide spectrum of applications in contactless processing and analysis of liquid samples (Trinh, Thiessen & Holt 1998;Yarin, Pfaffenlehner & Tropea 1998). The contactless manipulation and transportation of particles and droplets is one of the most interesting challenges in the acoustic levitation field (Koyama & Nakamura 2010;Foresti et al 2011;Foresti, Nabavi & Poulikakos 2012) with applications ranging from the handling of living cells in lab-on-a-chip devices (Bruus et al 2011) to millimetre-size sample manipulations in air (Bjelobrk et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Even SAW is known to be able to levitate objects, although for applications in motors, as reported by Asai and Kurosawa (2005), the gap that forms between the object and the SAW substrate is seen as a problem. Yarin et al (1998) provided a seminal analysis of the shape of levitated drops. With experimental results at 56 kHz for comparison and verification, they determined both the shape and displacement from the pressure node of 3-5 ' drops of n-hexadecane C 49 H 67 while exposed to ultrasound.…”
Section: Jetting and Levitationmentioning
confidence: 99%
“…Collas [18] showed results on acoustic levitation in ground experiments. Yarin et al [19] calculated acoustic radiation pressure using a boundary element method and predicted shapes of levitated droplets, which showed good agreement with experimental measurements. They showed that displacement of the droplet center relative to the pressure node due to the presence of gravity (or other steady force) was significant and could be computed.…”
Section: Previous Workmentioning
confidence: 78%